2022
DOI: 10.1186/s40104-022-00690-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of omega-3 polyunsaturated fatty acids, citrus pectin, and milk-derived exosomes on intestinal barrier integrity and immunity in animals

Abstract: The gastrointestinal tract of livestock and poultry is prone to challenge by feedborne antigens, pathogens, and other stress factors in the farm environment. Excessive physiological inflammation and oxidative stress that arises firstly disrupts the intestinal epithelial barrier followed by other components of the gastrointestinal tract. In the present review, the interrelationship between intestinal barrier inflammation and oxidative stress that contributes to the pathogenesis of inflammatory bowel disease was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 160 publications
0
6
0
11
Order By: Relevance
“…NF-κB is an important signaling pathway that activates intestinal epithelial cells to generate inflammation, providing a key target for the anti-inflammatory effects of bovine milk exosomes. 34,35 Our preliminary experiments comparing the immune response of exosomes from different processed milk sources in the same batch revealed that additional processing could impact exosome phenotypes, in which the effects on activation of cytokine release and inflammation inhibition differed. The current study further demonstrated that bovine milk exosomes inhibit the activity of the NF-κB signaling pathway in intestinal epithelial cells, attenuate p65 and IκBα protein phosphorylation, and reduce downstream TNF-α, IL-1β, and IL-6 release.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is an important signaling pathway that activates intestinal epithelial cells to generate inflammation, providing a key target for the anti-inflammatory effects of bovine milk exosomes. 34,35 Our preliminary experiments comparing the immune response of exosomes from different processed milk sources in the same batch revealed that additional processing could impact exosome phenotypes, in which the effects on activation of cytokine release and inflammation inhibition differed. The current study further demonstrated that bovine milk exosomes inhibit the activity of the NF-κB signaling pathway in intestinal epithelial cells, attenuate p65 and IκBα protein phosphorylation, and reduce downstream TNF-α, IL-1β, and IL-6 release.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that intestinal immune and epithelial structural cells are involved in the chronic inflammation underlying obesity, atherosclerosis, inflammatory bowel disease, and many other disorders, particularly in individuals consuming high-fat high-carbohydrate “Western” diet ( Arnone et al, 2021 ; Basson et al, 2021 ; Liu et al, 2021 ; Mukherjee et al, 2022 ; Nakanishi et al, 2021 ; Rescigno, 2014 ), and nearly one in two adults in the US is projected to be obese by 2030 ( Ward et al, 2019 ). The gastrointestinal tract is secured by a series of protective layers that physically separate the circulatory system from the external milieu, including a mucus layer, epithelium layer, and lamina propria layer ( Sundaram et al, 2022 ). Intestinal intraepithelial lymphocytes (IELs) are the major cell types that reside between the intestinal epithelial cells (IECs) forming the intestinal epithelium layer ( Olivares-Villagomez and Van Kaer, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Citrus pectin, a nonstarch polysaccharide, can help prevent constipation, improve intestinal homeostasis, and suppress intestinal inflammation. 20,21 Flavonoids including quercetin, naringin, and other flavonoids perform a protective role in the gut by maintaining the integrity of intestinal mucosa and balancing the composition of microbiota. [22][23][24] It has been proved that the flavonoids in citrus tangerine pith significantly reduce hypoxia-induced injury in intestinal smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%